Whole-genome sequencing in the investigation of recurrent invasive group A streptococcus outbreaks in a maternity unit. Issue 3 (March 2019) - Dickinson, H.; Reacher, M.; Nazareth, B.; Eagle, H.; Fowler, D.; Underwood, A.; Chand, M.; Chalker, V.; Coelho, J.; Daniel, R.; Kapatai, G.; Al-Shabib, A.; et al.
Summary: Background: The clinical manifestations of group A streptococcus (GAS) ( Streptococcus pyogenes ) are diverse, ranging from asymptomatic colonization to devastating invasive disease. Maternity-related clusters of invasive GAS (iGAS) infection are complex to investigate and control, especially if recurrent. Aim: To investigate three episodes of emm 75 GAS/iGAS infection in maternity patients at one hospital site over a four-year period (two with monophyletic ancestry). Methods: The episodes are described, together with whole-genome sequence (WGS) isolate analyses. Single nucleotide polymorphism differences were compared with contemporaneous emm 75 genomes. Findings: Over the four-year study period, seven mothers had emm 75 GAS/iGAS and one mother had emm 3 iGAS (in year 4) (subsequently discounted as linked). Three (clinical/screening samples) of the seven babies of emm -75-positive mothers and three screened healthcare workers were positive for emm 75 GAS. WGS similarity suggested a shared ancestral lineage and a common source transmission, but directionality of transmission cannot be inferred. However, the findings indicate that persistence of a particular clone in a given setting may be long term. Conclusions: Occupational health procedures were enhanced, staff were screened, and antibiotic therapy was provided to GAS-positive staff and patients. The definitive source of infection could not be identified, although staff–patient transmission was the most likely route. The pattern of clonal GAS transmission over the four-year study period suggests that long-term persistence of GAS may have occurred.